2015
DOI: 10.5414/np300789
|View full text |Cite
|
Sign up to set email alerts
|

The coexistence of dynamin 2 mutation and multiple mitochondrial DNA (mtDNA) deletions in the background of severe cardiomyopathy and centronuclear myopathy

Abstract: Dynamin2 (DNM2) gene mutations may result in Charcot-Marie-Tooth disease and centronuclear myopathy. Here, we present a patient suffering from cardiomyopathy and centronuclear myopathy with repetitive discharges and mild axonal neuropathy due to DNM2 mutation. Detailed cardiological and neurological examinations, electrophysiological tests, muscle biopsy, and molecular genetic analysis were performed. The patient developed left bundle branch block at age 40 and was fitted with a pacemaker at the age of 43. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
9
1
Order By: Relevance
“…In terms of genotype-phenotype relationship, we found that two genetically confirmed patients had additional heterozygous variants of other recessive myopathies. The coexistence of two causative genes in one patient has rarely been reported (23,24). These additional variants probably serve as a modifier for explaining the genotype-phenotype mismatching, although we did not find an add-on effect in this study.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In terms of genotype-phenotype relationship, we found that two genetically confirmed patients had additional heterozygous variants of other recessive myopathies. The coexistence of two causative genes in one patient has rarely been reported (23,24). These additional variants probably serve as a modifier for explaining the genotype-phenotype mismatching, although we did not find an add-on effect in this study.…”
Section: Discussioncontrasting
confidence: 65%
“…The coexistence of two causative genes in one patient has rarely been reported (23,24). The coexistence of two causative genes in one patient has rarely been reported (23,24).…”
Section: Discussionmentioning
confidence: 98%
“… 93) A patient with centronuclear myopathy due to a dynamin-2 mutation was also diagnosed with CMP. 94) At age 40, this patient subsequently developed left bundle-branch-block (LBBB), three years after which a pacemaker was implanted. 94) Early-onset dCMP in centronuclear myopathy may require HTX.…”
Section: Resultsmentioning
confidence: 99%
“…Since there were no significant abnormalities in the staining patterns of sarcolemmal proteins, muscular dystrophy was discounted; however, to our knowledge, the existence of CNM was not tested. Recent reports of human cases of CNM coexisting with cardiomyopathy ( Ceyhan-Birsoy et al, 2013 ; Agrawal et al, 2014 ; Gal et al, 2015 ) further highlight the importance of assessing the existence of CNM in skeletal muscles from patients with cardiomyopathy arising from PLN mutations.…”
Section: Discussionmentioning
confidence: 99%